Relokasi Pasar Tradisional dan Ketidakpastian Hukum Administrasi: Studi Kasus Pengelolaan Pasar Kowen Pasca-Perubahan Regulasi - Nurainun Mangunsong; Amalia Putri Afifah (UIN Sunan Kalijaga Yogyakarta, 2026)
Traditional markets serve as public spaces that integrate the economic, social, and cultural life of local communities, yet their existence is increasingly marginalized by modernization and the expansion of modern retail markets. This study examines the relocation of klitikan traders to Kowen Market in Sidokarto, Sleman, which has raised legal issues concerning legal certainty, authority legitimacy, and the protection of traders’ economic interests. Normatively, market management refers to Sleman Regional Regulation No. 3 of 2020, Regent Regulation No. 11 of 2015, and Government Regulation No. 11 of 2021 on Village-Owned Enterprises. However, institutional changes introduced by the latter regulation were not accompanied by adequate transitional arrangements at the regional level. This research employs a socio-legal method with a qualitative approach using field observations, interviews, and regulatory analysis. The findings reveal a significant administrative legal gap marked by regulatory disharmony, weak transition design, and institutional uncertainty. The study highlights the importance of adaptive and coherent administrative governance to ensure sustainable management of traditional markets.